Application of management control systems and leadership style on managerial performance - Choiri Choiri; Uswatun Khasanah; Zainab Zainab; Muchsin Zuhad Al'Asqolaini (International Journal of Applied Finance and Business Studies, 2023)
The purpose of this study is to determine the effect of the application of the management control system on managerial performance and to determine the effect of the application of the management control system and leadership style on managerial performance. This study used 6 (six) ecosystem companies PT Petrokimia Gresik in Gresik as samples. Determining the sample using non-probability techniques sampling. The independent and bound variables in this study were measured using Regression analysis. Based on the first hypothesis test, it can be concluded that the implementation of the management control system has an impact on the performance of PT Petrokimia Gresik's corporate ecosystem management. The second hypothesis based on hypothesis testing can be concluded that leadership style does not increase on managerial performance